MENGATASI KETERGANTUNGAN GADGET PADA REMAJA MELALUI EDUKASI POLA ASUH - Mawaddah, Nurul; Asma Chandrani Zafira Awan; Suhartanti, Ika (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Smartphone addiction level is defined as the level of addiction with excessive obsession with smartphone use.Listen their opinion, involved in the conversation, so little by little practice to be responsible to theirself. The purpose of this study was to determine the effect of democratic parenting education on gadget addiction on students of SMPN 3 Candi Sidoarjo The research method used was experimental research with pre-experimental method with the one-group pre-posttest design. The population in this study was the parents of students who were addicted to gadgets at SMPN 3 Candi Sidoarjo as many as 58. The sampling technique used was purposive sampling with a total of 20 respondents based on inclusion criteria. The measuring instrument used was a gadget addiction questionnaire. The results obtained in this study indicated that the respondents after being given the intervention experienced an increase were 4 people then the respondents with a declining category were 16 people. Analysis of the data used in this study using the Wilcoxon Signed Ranks Test, the results obtained p value = 0.001 with a alpha level of = 0.05, which means that there was a difference before and after being given democratic parenting education to parents of students who were addicted to gadgets at SMPN 3 Candi Sidoarjo. With the consistent implementation of democratic parenting, it can reduce the level of gadget addiction on students so that parents do not need to give too many rules that make children feel pressured and not confident.